2004
DOI: 10.1021/jp037674r
|View full text |Cite
|
Sign up to set email alerts
|

Is the Fukui Function a Right Descriptor of Hard−Hard Interactions?

Abstract: To verify whether the maximum or the minimum Fukui function site is better for protonation reactions or an altogether different local reactivity descriptor, viz., the charge is necessary, we calculate the Fukui functions (using a finite-difference approximation as well as a frozen-core approximation) and charges (Mulliken, Hirshfeld, and natural population analysis schemes) of several hydroxylamine derivatives, their sulfur-containing variants, and amino acids using B3LYP/6-311G(d,p) technique. While the Fukui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
127
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(135 citation statements)
references
References 18 publications
8
127
0
Order By: Relevance
“…The function f + (r) is a measure of reactivity toward a donor reagent (nucleophillic attack), f -(r) values measure reactivity toward an acceptor reagent (electrophilic attack) and an average value of both may be taken as a measure of reactivity toward a radical f 0 (r) [82]. Parr and Yang showed that sites in chemical species with the largest f(r) value are those with highest reactivity and are the preferred reaction site(s) [83][84][85]. Research has emphasised that hardness-softness f(r) derived from the DFT are powerful tools to predict active sites of a molecule [84,86,87].…”
Section: Dft Reactivity Modelling Procedures With the Fukui Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The function f + (r) is a measure of reactivity toward a donor reagent (nucleophillic attack), f -(r) values measure reactivity toward an acceptor reagent (electrophilic attack) and an average value of both may be taken as a measure of reactivity toward a radical f 0 (r) [82]. Parr and Yang showed that sites in chemical species with the largest f(r) value are those with highest reactivity and are the preferred reaction site(s) [83][84][85]. Research has emphasised that hardness-softness f(r) derived from the DFT are powerful tools to predict active sites of a molecule [84,86,87].…”
Section: Dft Reactivity Modelling Procedures With the Fukui Functionmentioning
confidence: 99%
“…Parr and Yang showed that sites in chemical species with the largest f(r) value are those with highest reactivity and are the preferred reaction site(s) [83][84][85]. Research has emphasised that hardness-softness f(r) derived from the DFT are powerful tools to predict active sites of a molecule [84,86,87]. The f(r) defines the reactivity of an atom in a molecule and, together with local softness, are suitable to describe reactivity of different substrates [88], including symmetrical char structures.…”
Section: Dft Reactivity Modelling Procedures With the Fukui Functionmentioning
confidence: 99%
“…[65] This "minimum Fukui function rule" has been broadly applied, [69][70][71] but also criticized as overly simplistic. [67,72] Klopman asserts that hard-hard interactions are predominately ionic in nature, and so electrostatic effects dominate and frontier-orbital effects are relatively unimportant. The minimum Fukui function principle captures the irrelevance of the frontier orbitals but misses the fact that electrostatic interactions normally dominate hard-hard interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The minimum Fukui function principle captures the irrelevance of the frontier orbitals but misses the fact that electrostatic interactions normally dominate hard-hard interactions. [67,68,72] In contrast to the well studied local softness, few studies of the local hardness are reported in the literature, mainly by our group using the local hardness as an indicator for charge concentration in studies on zeolite-catalyzed reactions, [73][74][75] noncovalent intermolecular interactions, [76][77][78][79][80] and local HSAB. [81] Then, one of the goals of this work is to see if the local hardness is able to locate the hardest reactive sites in a molecule.…”
Section: Introductionmentioning
confidence: 99%
“…These parameters, called reactivity descriptors, defined within the framework of density functional theory are global hardness (g) (also called chemical hardness), electrophilicity (x), chemical potential (l) etc [21]. These descriptors have been tested and studied extensively by several research groups and are reported to be very useful in rationalizing the reactivity patterns in the molecular systems [22][23][24][25][26]. Geerlings et al and Chattaraj et al have reviewed the theoretical basis of these descriptors and also their applicability [27,28].…”
Section: Introductionmentioning
confidence: 99%